UJI ADAPTASI BEBERAPA VARIETAS PADI SAWAH (Oryza sativa L) DAN KAPUR DOLOMIT PADA TANAH GAMBUT - Hercules Gultom; Mardaleni Mardaleni (UIR Press, 2014)
Adaptation test of several rice varieties and dolomit lime on peatland was carried out in the greenhouse of Faculty of Agriculture Riau Islamic University Pekanbaru. The purpose of this research ws to know adaptation power several yielding rice varieties on peatland with using dolomit and to obtain yielding rice varieties which is able to adapt with peatland, and to find a correct dosage by using doomit lime for raise pH soil. The experiment was arranged with grouply randomized design with two factors. The first factor was yielding rice varieties, consisting of four factors: V1 (IR 64), V2 (IR-72), V3 (Kapuas), and V4 (Santani). The second factor was dolomit lime, consisting of four factors: d1 (2.56 t/ha) and PH 5.6, D2 (3.60 t/ha and pH 5.4, D3 (4.51 t/ha) and pH 5.2, and D4 (5.49 t/ha) and pH 5.0. The parameter observed were plant height, number of productive shoot, percetage of unhask full rice, weight of dry rice per hectare, and weight of 1000 seeds. The resuts showed interaction using several yielding rice varieties was not significant effect on the observed parameters. However, the use of yielding varities showed a significant effect with the best variety: V1 (3.9 t/ha), V2 (3.8 t/ha), V3 (3.1 t/ha), and V4 (3.1 t/ha). While, the use of dolomit lime was affected significantly for the whole parameters with the best parameter: D1 (3,6 t/ha), D2 (3,6 t/ha), D3 (3,4 t/ha), and D4 (3,3 t/ha).